BK virus-associated viruria and viremia in a patient with lymphangioleiomyomatosis after lung re-transplantation: A case report and review of the literature on BK virus infection post-lung transplantation. Issue 10 (October 2019) - Okumura, Junya; Nakahara, Yoshio; Nakaguro, Masato; Shindo, Yuichiro; Hase, Tetsunari; Wakahara, Keiko; Hashimoto, Naozumi; Hasegawa, Yoshinori
Abstract: The BK virus (BKV) is a member of the polyomaviridae family of DNA viruses. BKV reactivates under a highly immunosuppressed state and causes renal dysfunction. In renal transplant patients, BKV infection leads to tubular impairment and loss of transplanted kidney grafts. However, few studies have reported on the relationship between BKV and lung transplantation. Adjustment of the dosage of immunosuppressants is needed in some cases, but the treatment method has not been established. Here, we report a case of BKV-associated viruria and viremia in a patient with lymphangioleiomyomatosis (LAM) after lung re-transplantation. A 44-year-old female refractory LAM patient who had undergone lung re-transplantation 3 months earlier was diagnosed with BKV-associated viruria and viremia. Urine cytology indicated decoy cells and the urine and serum polymerase chain reaction test was positive for BKV. As scheduled after re-transplantation surgery, immunosuppressive drugs were progressively reduced. This patient was considered to have experienced spontaneous BKV-associated viremia and viruria. Review of the literature suggested that 17%–42% of BKV-associated viruria cases have been reported after lung transplantation, but cases of BKV-associated nephropathy are rarely reported. Based on the present case, doctors involved in lung transplantation should monitor patients for BKV infection. Decoy cell monitoring by urine cytology is a useful screening method in the follow-up observation after lung transplantation. Early-stage interventions may prevent BKV-associated nephropathy even in patients who have developed BKV viremia, and sirolimus can be administered to patients with histories of BKV infection if they are carefully monitored.